Justice Initiatives - Petrial Detention - (:unkn) unknown (My University, 2016)
A publication of the Open Society Justice Initiative. In 2006, an estimated 7.4 million people around the world were held in detention while awaiting trial—a practice that violates international norms, wastes public resources, undermines the rule of law, and endangers public health. This issue of Justice Initiatives looks at the global over-reliance on pretrial detention and examines the challenges of reducing and reforming its use.